2019
DOI: 10.1111/ele.13257
|View full text |Cite
|
Sign up to set email alerts
|

Proximity of restored hedgerows interacts with local floral diversity and species' traits to shape long‐term pollinator metacommunity dynamics

Abstract: Disconnected habitat fragments are poor at supporting population and community persistence; restoration ecologists, therefore, advocate for the establishment of habitat networks across landscapes. Few empirical studies, however, have considered how networks of restored habitat patches affect metacommunity dynamics. Here, using a 10‐year study on restored hedgerows and unrestored field margins within an intensive agricultural landscape, we integrate occupancy modelling with network theory to examine the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 67 publications
(114 reference statements)
4
32
1
Order By: Relevance
“…Importantly, this is also the scale at which farmers make decisions about planting, and therefore has the largest implications for rapid changes on private lands. Native hedgerows, the primary method for farmers to plant new woody vegetation along field margins, are also an important sources of pollination services for sunflowers (Sardiñas et al, 2016) and support pollinator metacommunity dynamics (Ponisio et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this is also the scale at which farmers make decisions about planting, and therefore has the largest implications for rapid changes on private lands. Native hedgerows, the primary method for farmers to plant new woody vegetation along field margins, are also an important sources of pollination services for sunflowers (Sardiñas et al, 2016) and support pollinator metacommunity dynamics (Ponisio et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The multispecies multiseason example is from Ponisio, Valpine, and MGonigle, L.K. & Kremen, C. (), a study surveying a bee community across restored habitat in Northern California, USA, and a large number of explanatory variables and their interactions on detection, colonization, and persistence (Table , Appendix ). Finally, for an example N‐mixture model, we followed the example of Kéry and Royle () modeling the abundance of great tits from breeding bird survey data across Switzerland (Table , Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence documenting this function includes hedgerow-promoted movement of butterflies [123], moths [114], flies [53] and bees [115,116]; and butterfly travel along windbreaks [121] and riparian buffers [48]. A network of hedgerows was found to support wild bee species' richness and functional diversity [71] and the establishment and maintenance of populations at the landscape scale [157]. Syrphid flies were more abundant in forest-connected hedgerows than in forest edges with isolated hedges being intermediate [53].…”
Section: Landscape Connectivitymentioning
confidence: 99%
“…None of the studies reviewed found evidence that hedgerows or windbreaks reduced pollinators in crops or crop pollination by concentrating pollinators in the agroforestry practice. Habitat connectivity benefits can be higher when this semi-natural habitat is added to more homogenous and intensely managed fields and landscapes [21,157,158].…”
Section: Site Connectivitymentioning
confidence: 99%